The effect of inter-incisal opening on the energy delivered by light curing unit to simulated dental restorations - Harun, Nor Asilah (IIUM Press, International Islamic University Malaysia, 2017)
The development of the enamel acid-etch technique, the resin system based on BisGMA and dentine bonding have resulted in the extensive use of composite resins in dentistry. Advancements in composite resins as restorative materials have led to significant changes in the management of dental hard tissue disease. When used together with a bonding system, composite resins (CRs) adhere to dental tissue and hence they do not depend on cavity design for retention. This has resulted in a change in cavity design, with smaller cavities and the preservation of tooth structure. Aesthetically, composite resins have been made in a wide range of tooth coloured shades allowing nearly invisible restoration.